Unraveling gut microbiome alterations and metabolic signatures in hereditary transthyretin amyloidosis - Hanyu Li; Zeyuan Wang; Shan He; Xinyue Zhao; Qingyang Wu; Yueshen Sun; Yue Fan; Xiaomin Hu; Zhuang Tian; Shuyang Zhang (Microbiology Spectrum, 2025)
ABSTRACT Hereditary transthyretin amyloidosis (hATTR) is a rare, often fatal disease characterized by the abnormal aggregation of atypical transthyretin fibrils. Given the variability in the penetrance and clinical manifestations of hATTR, the role of nongenetic factors, particularly those related to the gut microbiota, warrants investigation. We conducted a cross-sectional study, examining the untargeted serum metabolome and gut metagenome in 13 patients with hATTR and 22 healthy controls. Significant disparities were observed in both the serum metabolome and gut microbiome of individuals with hATTR when compared to healthy controls. Notably, the serum levels of gamma-aminobutyric acid (GABA) and taurine were markedly decreased in the hATTR group, with the most pronounced reduction in those exhibiting hATTR-related cardiac amyloidosis. Additionally, commensals such as Bifidobacterium pseudocatenulatum, Lactobacillus rogosae, and Hungatella hathewayi were significantly diminished in hATTR patients and were positively correlated with the metabolite module containing GABA and taurine. Metagenomic and metabolomic pathway enrichment analyses collectively revealed disruptions in glutamate and taurine metabolism in hATTR. Our findings imply that patients with hATTR may exhibit metabolic irregularities in glutamate and taurine, potentially associated with an imbalance in the gut microbiota.IMPORTANCEHereditary transthyretin amyloidosis (hATTR) is influenced not only by genetic factors but also by environmental or host factors during its onset and progression. Previous studies have independently examined the metabolome or gut microbiome in hATTR, but the interplay between the microbiota and metabolism under this condition remains largely unknown. Our cross-sectional study represents the first comprehensive integration of gut metagenome and serum metabolome analyses in hATTR patients. We observed disturbances in glutamate and taurine metabolism among these patients, which correlated with distinctive shifts in the gut microbiota. This study offers insights into the intricate dynamics among gut dysbiosis, metabolic imbalances, and the progression of hATTR, suggesting directions for future research into the underlying mechanisms and therapeutic strategies.